2017
DOI: 10.1016/j.ymthe.2017.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Nitric Oxide as Targeted Anti-biofilm Adjunctive Therapy to Treat Chronic Pseudomonas aeruginosa Infection in Cystic Fibrosis

Abstract: Despite aggressive antibiotic therapy, bronchopulmonary colonization by Pseudomonas aeruginosa causes persistent morbidity and mortality in cystic fibrosis (CF). Chronic P. aeruginosa infection in the CF lung is associated with structured, antibiotic-tolerant bacterial aggregates known as biofilms. We have demonstrated the effects of non-bactericidal, low-dose nitric oxide (NO), a signaling molecule that induces biofilm dispersal, as a novel adjunctive therapy for P. aeruginosa biofilm infection in CF in an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
135
0
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(146 citation statements)
references
References 68 publications
(84 reference statements)
2
135
0
9
Order By: Relevance
“…however NO microelectrodes are highly sensitive and offer excellent spatial and temporal resolution in tissues or body fluids. A proof-of-concept preclinical study using low-dose gaseous NO in the pM to nM range, has recently shown to reduce the size of the P. aeruginosa biofilm aggregate in sputum as a primary clinical outcome in a small number of patients with cystic fibrosis 68 . Patients did not exhibit adverse effects to NO therapy.…”
Section: Inducing Biofilm Dispersalmentioning
confidence: 99%
“…however NO microelectrodes are highly sensitive and offer excellent spatial and temporal resolution in tissues or body fluids. A proof-of-concept preclinical study using low-dose gaseous NO in the pM to nM range, has recently shown to reduce the size of the P. aeruginosa biofilm aggregate in sputum as a primary clinical outcome in a small number of patients with cystic fibrosis 68 . Patients did not exhibit adverse effects to NO therapy.…”
Section: Inducing Biofilm Dispersalmentioning
confidence: 99%
“…By inducing dispersal of the biofilm with NO, the physical barrier imposed by the EPS matrix can be negated entirely. Research has shown that the dispersed cells are considerably more susceptible to antimicrobial treatments; it can therefore be inferred that adjuvant NO potentiates antibiotics against biofilms (Howlin et al ., ). Utilizing the spontaneous NO donor sodium nitroprusside (SNP), Howlin et al .…”
Section: The Applications Of Nitric Oxide For the Treatment Of Bactermentioning
confidence: 97%
“…Utilizing the spontaneous NO donor sodium nitroprusside (SNP), Howlin et al . () successfully showed that NO disrupted P. aeruginosa biofilms from cystic fibrosis sputum samples in vitro . The same study also highlighted the importance of dispersal as a means of therapy, since the administration of the antibiotic tobramycin alone caused a significant increase in biomass and biofilm thickness compared to untreated controls.…”
Section: The Applications Of Nitric Oxide For the Treatment Of Bactermentioning
confidence: 99%
See 1 more Smart Citation
“…The free radical NO is another innate immune component with a broad concentration-dependent activity against microbes ranging from a signaling molecule-like anti-biofilm to a bactericidal activity [9, 10]. Williams and Boon [11] describe the anti-biofilm molecular mechanisms of action to be surprisingly convergent in different bacteria with NO being consistently sensed by two types of conserved sensors covalently or noncovalently connected downstream to a quorum sensing and/or second messenger cyclic di-GMP signaling output [12].…”
mentioning
confidence: 99%